Próba analizy efektywności wybranych strategii gospodarczych dla krajów rozwijających się - Dziadosz, Przemysław (An Attempt the Analysing of Effectiveness of Some Economic Strategies for Developing Countries, 2005)
The issue of impact of B&R on a national economic growth is facing economic policy-makers from almost late 60s. Nowadays this subject is essential especially for developing countries that generally are seeking for their own way to achieve an effective catch up policy. Developed countries have sound evidence that innovations, which are effect of R&D expenditures, are significant factor for their economic growth. Based on this experience they (i.e. OECD, World Bank, European Commission) strongly recommend the developing strategies based on intensive B&R expenditures according to the rule: the more investing in B&R, the more economic growth achieved.Therefore, my approach has been to review relevant literature in the light of internal experience of evaluating and pinpoint thus who has alternative evidence or theory. I have focused on the 'innovation' literature which tends to take economic theories and research of the innovation as its point of long run source for the economic growth. This paper is an attempt of evaluation, which one from the chosen strategies is more effective and therefore suitable for developing countries.There are two principal ways to obtain innovations essential for the national economic growth; by own R&D expenditures or/and by technologies transfer. Over the past twenty or thirty years, it has been increasingly recognized that innovation involves a great deal more than creating and selling 'standard goods'. It is a process that happens in an economic and social context, and is no longer seen as an 'automatic' result of investing in R&D. Successive generations of 'innovation models' have characterized innovation as increasingly complex and bound up with socioeconomic factors such as market linkage and match with the available infrastructure and human capital. The technologies transfer literature makes it clear also that technology is more than a 'black box' but depends on its social and infrastructural context. If technology is transferred into contexts for which it is not fitted, it will fail to work. From the other hand, technologies transfer seems to be much more effective part of catch up policy than intensive R&D expenditures for innovations. Developing country policy-makers suppose to hang in the balance which strategy is more effective for the economic growth acceleration in the light of given arguments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 145-152